2017
DOI: 10.1007/s10461-017-1964-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex, PrEP, and Stigma: Experiences with HIV Pre-exposure Prophylaxis Among New York City MSM Participating in the HPTN 067/ADAPT Study

Abstract: The HPTN 067/Alternative Dosing to Augment Pre-Exposure Prophylaxis Pill Taking (ADAPT) study evaluated daily and non-daily dosing schedules for oral pre-exposure prophylaxis (PrEP) to prevent HIV. A qualitative sub-study including focus groups and in-depth interviews was conducted among men who have sex with men participating in New York City to understand their experience with PrEP and study dosing schedules. The 37 sub-study participants were 68% black, 11% white, and 8% Asian; 27% were of Hispanic/Latino e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 41 publications
9
58
0
Order By: Relevance
“…Our findings about stigma are consistent with previous research identifying stigma as an important factor influencing PrEP use (Arnold et al, 2017;Collins, McMahan, & Stekler, 2017;Franks et al, 2018;García & Harris, 2017;Grace et al, 2018;Haire, 2015;Liu et al, 2014;Taylor et al, 2014;Thomann et al, 2018;. In our and other studies, PrEP stigma is closely tied to stigma around HIV, "risky" sexual behavior, and sexual and gender identity (Franks et al, 2018;Grace et al, 2018;Haire, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings about stigma are consistent with previous research identifying stigma as an important factor influencing PrEP use (Arnold et al, 2017;Collins, McMahan, & Stekler, 2017;Franks et al, 2018;García & Harris, 2017;Grace et al, 2018;Haire, 2015;Liu et al, 2014;Taylor et al, 2014;Thomann et al, 2018;. In our and other studies, PrEP stigma is closely tied to stigma around HIV, "risky" sexual behavior, and sexual and gender identity (Franks et al, 2018;Grace et al, 2018;Haire, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Some participants did note that they might be less likely to use condoms or more likely to engage in casual sex than if they were not on PrEP. However, similar to other research, other participants described having fewer sexual partners because PrEP use led to more thoughtful decision-making about sexual behavior and risk (Arnold et al, 2017;Franks et al, 2018;Sagaon-Teyssier et al, 2016). Arnold and colleagues (2017) also noted increased discussion of safer sex with partners, which many participants in our study reported.…”
Section: Discussionsupporting
confidence: 85%
“…Women in South Africa have cited support from male partners and family members as a facilitator of PrEP use, and have described PrEP stigma, relationship power dynamics and issues around product disclosure as barriers to PrEP use [45]. Similar concerns about stigma and disclosure have been described in programmatic PrEP delivery settings among heterosexual HIV serodiscordant couples in Nigeria and MSM in the United States, particularly when PrEP is explicitly marketed for "high-risk populations" [14,46,47]. Mediation analyses among MSM and transgender women in the United States have shown that stigma has a direct negative association on PrEP adherence and an indirect influence on PrEP use through fears about disclosure, highlighting the importance of both stigma and disclosure on regular PrEP use [22], although similar analyses are needed among African AGYW.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to AMPrEP being a demonstration project where costs and other structural barriers played no role. Furthermore, social‐environmental factors such as stigma, that are known to play a role in the motivation to start or temporarily stop PrEP use , may play less of a role once the decision to start PrEP was already taken.…”
Section: Discussionmentioning
confidence: 99%